Self-assembled photonic structure: a Ga optical antenna on GaP nanowires. Issue 5 (13th January 2023) - Kuznetsov, Alexey; Roy, Prithu; Grudinin, Dmitry V.; Kondratev, Valeriy M.; Kadinskaya, Svetlana A.; Vorobyev, Alexandr A.; Kotlyar, Konstantin P.; Ubyivovk, Evgeniy V.; Fedorov, Vladimir V.; Cirlin, George E.; Mukhin, Ivan S.; Arsenin, Aleksey V.; et al.
Abstract : Effects promoted by a Ga optical nanoantenna on self-assembled GaP nanowires including field confinement, enhanced internal reflection and antenna effect are explored. The perspectives for nanophotonic emitters, waveguides and couplers are discussed. Abstract : Semiconductor nanowires are the perfect platform for nanophotonic applications owing to their resonant, waveguiding optical properties and technological capabilities providing control over their crystalline and chemical compositions. The vapor–liquid–solid growth mechanism allows the formation of hybrid metal-dielectric nanostructures promoting sub-wavelength light manipulation. In this work, we explore both experimentally and numerically the plasmonic effects promoted by a gallium (Ga) nanoparticle optical antenna decorating the facet of gallium phosphide (GaP) nanowires. Raman, photoluminescence and near-field mapping techniques are used to study the effects. We demonstrate several phenomena including field enhancement, antenna effect and increase in internal reflection. We show that the observed effects have to be considered when nanowires with a plasmonic particle are used in nanophotonic circuits and discuss the ways for utilization of these effects for efficient coupling of light into nanowire waveguide and field tailoring. The results open up promising pathways for the development of both passive and active nanophotonic elements, light harvesting and sensorics.